The The Effect Of Using ChatGPT Application To Improve Students' Speaking Ability At The Eleventh Grade Students Of SMAN 9 Mandau - Jufriadi (Jolly Journal of English Education, 2024)
This study was a quantitative approach with quasi-experimental research design. The descriptive quantitative methods was applied to describe the data. The research population was all class eleventh grade students, totaling 291 students consisting of 9 classes. Due to the large number of population, the researcher took a sample of 54 students. In this research, it was found that the mean of pre-test score in experimental class was 62.07 and in control class was found 60. Meanwhile, the mean of post-test score which found in experimental class was 74.86 and in control class was 68. It can be concluded that there were differences in the average of the students’ speaking ability at the time of pretest and posttest. It meant there was significant effect on students’ speaking ability by ChatGPT Application.